Phenotypic attributes and production performances of Agonda Goan pig - CHAKURKAR, EAKNATH B; SAHU, AMIYA RANJAN; P, GOKULDAS P; BANIK, SANTANU; NAIK, SAJAN (The Indian Journal of Animal Sciences, 2023)
The aim of study was to evaluate morphometric traits, growth and reproduction performance of indigenous Agonda Goan pigs reared under coastal climate which supports livelihood development of resource poor farmers. Population size in breeding tract varied depending on farmers’ preference for breeding and consumers’ demand for pork. Data (n=74) on different parameters were recorded both from farmer’s flock and institute pig unit. Body measurements such as body length, height at withers, chest girth and neck girth of both were measured using measuring tape. The body weights at different ages i.e., birth, weaning and monthly interval up to one year of age were recorded using digital weighing balance. The average body length, chest girth, height at withers and neck girth were 102.68±3.22 cm, 99.86±3.64 cm, 58.32±1.19 cm and 73.09±4.18 cm, respectively. The mean bristle yield (g/cutting), bristle length(cm) and bristle diameter (micron) were 38.08±5.85, 4.45±0.04 and 268.21±9.84 in males, and 88.16±16.95, 5.69±0.07 and 270.93±11.07 in female pigs, respectively. The mean weight at birth was 0.59±0.01 kg and at weaning was 3.76±0.12 kg. The yearling weights of adult male and female were 46.58±4.50 and 47.27±6.46 kg, respectively. The average litter size at birth and at weaning was 7.21±0.41 and 5.93±0.28, respectively. Pre-weaning and postweaning growth rates were 79.25±9.86 and 153.85±13.34 g/day, respectively. This unique germplasm has potential for sustainable production with improved pig breeding programs. However, the breed is under constant threat due to indiscriminate crossbreeding with unbalanced admixture and replacement with exotic breeds for which immediateconservation and improvement programs are essential to save the breed.